Gravidez na adolescência e o contexto escolar na cidade de Goioerê - Vechi, Anderson de (2015)
Adolescence is a transition phase between childhood and adulthood, which is the object of study in various fields such as Education, Science, Biology and Health. But at this stage of life that occur to the structure of the personality of the physical changes caused by production of sex hormones, which act in certain areas of the human body and enable the body for reproduction. The various biological changes correspond to early adolescence, which is called puberty. So the main study of the subject related to the theme was seeking to clarify the existence of cases of teenage pregnancy in the city of Goioerê. However the rate of teenage pregnancy and sexually transmitted diseases has increased over time. But find out if this fact may be occurring and whether a relationship exists for faults in sex education. This paper aims to provide some concepts about human sexuality and through this propose a project aimed at students of elementary and high school. Noting the lack of knowledge of adolescent girls before the fact of early pregnancy, visualizing the most frequent social class and the influence of sex education acquired in the interim. Seeking to know knowledge of contraceptive methods by adolescents. Noting the involvement of society and the family on the sexuality of the process in the education of adolescents. Therefore, a thorough literature about adolescence and issues related to this phase and about sexuality in schools was held.